HPV16 E6-Activated OCT4 Promotes Cervical Cancer Progression by Suppressing p53 Expression via Co-Repressor NCOR1 - Shu, Shujuan; Li, Zhi; Liu, Liu; Ying, Xia; Zhang, Yina; Wang, Ting; Zhou, Xiaoye; Jiang, Peiyue; Lv, Weiguo (Frontiers in Oncology, 2022)
Human papillomaviruses (HPV), mainly HPV16 and HPV18, of high-risk classification are involved in cervical cancer carcinogenesis and progression. Octamer-binding transcription factor 4 (OCT4) is a key transcription factor that is increased in various cancer types. Cervical cancer patients with higher levels of OCT4 had worse survival rates. However, the definite mechanisms underlying its function in the development of cervical cancer still remain to be explicated. Here, our study demonstrated that OCT4 expression was slightly increased in cervical cancer tissues than in precancerous ones. However, OCT4 was significantly upregulated in HPV16-positive tissues, in contrast to the expression profiling for p53. Moreover, knockdown of HPV16 E6 in SiHa cells suppressed the expression of OCT4 with impaired activities of cell proliferation, migration, and invasion, while it recovered the expression of p53. Overexpression of OCT4 and p53 exerted opposite roles on cell proliferation, migration, invasion, and colony formation of cervical cancer cells. More importantly, the enforced expression of OCT4 augmented p53-inhibited cell migration, invasion, and colony formation in human cervical cancer by promoting EMT. Finally, we identified that OCT4 could bind to the p53 promoter region to repress p53 expression by recruiting co-repressor NCOR1 using luciferase, ChIP, and co-IP experiments. We further illustrated that OCT4 not only increased the lung metastasis of cervical cancer but also effectively reversed p53-inhibited lung metastasis. In conclusion, our results suggested that HPV16 E6 activated the expression of OCT4 and subsequently crippled the transcription of p53 via co-repressor NCOR1, which contributed to cervical cancer progression.